ABU SALABIKH – ABSOLUTE RADIOCARBON CHRONOLOGY. (December 2021) - Wencel, Maciej M.
Abstract : This article presents a new absolute chronology for the archaeological site of Abu Salabikh, Southern Iraq, during the 4 th and 3 rd millennia BC. The main goals of this study were to synchronise the sequences of the West and Main Mounds, corroborating the dating schemes based on archaeological and textual finds, and assigning an absolute date to the transition between Uruk and Early Dynastic (ED) periods. Previously published dates and newly produced 14 C measurements were used in tandem with Bayesian statistical models to arrive at more precise time estimates. Some inconsistencies in the results point to possible disturbance of the archaeological sequence in the context of tannur kilns and highlight the need for careful sample collection and selection methodology. The results suggest a hiatus in settlement between the Uruk and ED periods c. 3000 BC, and confirm the date of c. 2650-2500 BC for the Early Dynastic ED IIIa Fara-style texts.